Ocular pharmacokinetics and tolerability of bimatoprost ophthalmic solutions administered once or twice daily in rabbits, and clinical dosing implications [Corrigendum] - Shen J (Dove Medical Press, 2018)
Shen J, Goodkin ML, Tong W, Attar M. Clin Ophthalmol. 2017;11:1761–1767.On page 1765, Clinical correlation with evidence for use of bimatoprost twice daily in humans section, second column, last line, “−5.4 to −5.6 mm Hg” should have read “−5.4 to −6.0 mm Hg”.Read the original article